Comparison Of Anthropometric Indicator of General Obesity (BMI) To Anthropometric Indicators of Central Obesity (WC, WHR) In Relation to Diabetes Mellitus in Male Population - Patel, Divyangkumar N; Singh, M P (National Journal of Community Medicine, 2013)
Objective: -To evaluate and compare predictor for Diabetes mellitus among anthropometric indicators of obesity (Body Mass Index, Waist circumference and Waist to Hip Ratio). Method: - The present study was conducted among policemen of the Bhavnagar city, total 260 policemen of ≥ 30 years of age included in the study (Response rate 83 %). The fasting and 2 hour postprandial blood glucose test was done for diagnosis of the diabetes and According to American Diabetes Association (2004) criteria subjects was diagnosed as a diabetic, prediabetic (Impaired Fasting Glucose and Impaired Glucose Tolerance) and normoglycemic. BMI, waist circumference and Waist to hip ratio of every subject was measured. Receiver operator characteristic curve was constructed to determine the optimal value of each parameter to diagnose the diabetes and compare the all three anthropometric indicator for predicting the diabetes. Result: Higher area under curve was found with WHR, than WC and lowest with BMI. It was 0.764, 0.751, and 0.611 for WHR, WC and BMI respectively. Optimum cut off points for predicting diabetes are 0.948, 98 cm and 25 for WHR, WC and BMI respectively. Higher Youden index found for WHR and WC than BMI. Conclusion: our study shows that the anthropometric indicators of central obesity (WHR and WC) are better predictive of diabetes mellitus than Anthropometric indicator of general obesity (BMI).